Metric networks for enhanced perception of non-local semantic information - Li, Jia; Zhou, Yu-qian; Zhang, Qiu-yan (Frontiers in Neurorobotics, 2023)
Metric learning, as a fundamental research direction in the field of computer vision, has played a crucial role in image matching. Traditional metric learning methods aim at constructing two-branch siamese neural networks to address the challenge of image matching, but they often overlook to cross-source and cross-view scenarios. In this article, a multi-branch metric learning model is proposed to address these limitations. The main contributions of this work are as follows: Firstly, we design a multi-branch siamese network model that enhances measurement reliability through information compensation among data points. Secondly, we construct a non-local information perception and fusion model, which accurately distinguishes positive and negative samples by fusing information at different scales. Thirdly, we enhance the model by integrating semantic information and establish an information consistency mapping between multiple branches, thereby improving the robustness in cross-source and cross-view scenarios. Experimental tests which demonstrate the effectiveness of the proposed method are carried out under various conditions, including homologous, heterogeneous, multi-view, and cross-view scenarios. Compared to the state-of-the-art comparison algorithms, our proposed algorithm achieves an improvement of approximately 1%, 2%, 1% and 1% in terms of similarity measurement Recall@10, respectively, under these four conditions. In addition, our work provides an idea for improving the cross-scene application ability of UAV positioning and navigation algorithm.